2023
DOI: 10.3390/plants12010202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Composition of Biologically Active Compounds during the Ripening Period in Fruit of Different Large Cranberry (Vaccinium macrocarpon Aiton) Cultivars Grown in the Lithuanian Collection

Abstract: In our investigation, we evaluated the content of chlorogenic acid, proanthocyanidins, anthocyanins, flavonols, triterpenoids, and phytosterols in cranberry fruit extracts of the cultivars ‘Baifay’, ‘Early Black’, ‘Howes’, ‘Pilgrim’, ‘Red Star’, and ‘Stevens’ grown in Lithuania, as well as changes in the antioxidant activity in extracts of fruit samples of these cultivars during the period of berry maturation. The highest amount of proanthocyanidins (8.87 ± 0.57 mg EE/g EE) and flavonols (3688.52 ± 22.85 µg/g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Another important group of bioactive compounds in cranberry fruits that determines the biological effects of fruit preparations are flavanols. A comparative analysis of the qualitative and quantitative composition of flavonols in V. macrocarpon and V. oxycoccos fruit samples showed that the total flavonol content (1465.56 ± 31.22 µg/g to 3688.52 ± 22.85 µg/g) in the large cranberry fruit samples varied more widely than the total flavonol content (518 ± 16 µg/g to 2811 ± 31 µg/g) in the small cranberry fruit samples [ 28 ]. In a study by Šedbarė et al, the quantitative composition of flavonols in V. macrocarpon fruit samples (quercetin-3-galactoside—29.07–33.87%, myricetin-3-galactoside—22.73–33.73%, quercetin-3-α-L-arabinofuranoside—14.55–19.88%, quercetin-3-rhamnoside—7.15–17.76%, quercetin-3-arabinopyranoside—2.13–3.44%, isoquercetin—0.98–4.73%, quercetin—0.91–3.80%, and myricetin—0.67–2.27%) was consistent with the quantitative composition of the flavonols found in fruit samples of V. oxycoccos [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another important group of bioactive compounds in cranberry fruits that determines the biological effects of fruit preparations are flavanols. A comparative analysis of the qualitative and quantitative composition of flavonols in V. macrocarpon and V. oxycoccos fruit samples showed that the total flavonol content (1465.56 ± 31.22 µg/g to 3688.52 ± 22.85 µg/g) in the large cranberry fruit samples varied more widely than the total flavonol content (518 ± 16 µg/g to 2811 ± 31 µg/g) in the small cranberry fruit samples [ 28 ]. In a study by Šedbarė et al, the quantitative composition of flavonols in V. macrocarpon fruit samples (quercetin-3-galactoside—29.07–33.87%, myricetin-3-galactoside—22.73–33.73%, quercetin-3-α-L-arabinofuranoside—14.55–19.88%, quercetin-3-rhamnoside—7.15–17.76%, quercetin-3-arabinopyranoside—2.13–3.44%, isoquercetin—0.98–4.73%, quercetin—0.91–3.80%, and myricetin—0.67–2.27%) was consistent with the quantitative composition of the flavonols found in fruit samples of V. oxycoccos [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis of the qualitative and quantitative composition of flavonols in V. macrocarpon and V. oxycoccos fruit samples showed that the total flavonol content (1465.56 ± 31.22 µg/g to 3688.52 ± 22.85 µg/g) in the large cranberry fruit samples varied more widely than the total flavonol content (518 ± 16 µg/g to 2811 ± 31 µg/g) in the small cranberry fruit samples [ 28 ]. In a study by Šedbarė et al, the quantitative composition of flavonols in V. macrocarpon fruit samples (quercetin-3-galactoside—29.07–33.87%, myricetin-3-galactoside—22.73–33.73%, quercetin-3-α-L-arabinofuranoside—14.55–19.88%, quercetin-3-rhamnoside—7.15–17.76%, quercetin-3-arabinopyranoside—2.13–3.44%, isoquercetin—0.98–4.73%, quercetin—0.91–3.80%, and myricetin—0.67–2.27%) was consistent with the quantitative composition of the flavonols found in fruit samples of V. oxycoccos [ 28 ]. Wang et al investigated the flavonol composition of V. macrocarpon fruit samples and found that the amount of quercetin-3-galactoside was 31–46%, the amount of myricetin-3-galactoside—19–32%, the amount of quercetin-3-α-L-arabinofuranoside—7–17%, and the amount of quercetin-3-rhamnoside—7–14% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations